The Economics of Health and Vitamin Consumption. (4th November 2012) - Schroeter, Christiane; Anders, Sven; Carlson, Andrea
Abstract: We estimate the impact of vitamin supplement intake, lifestyle, health indicators, food culture, and demographics on diet quality outcomes as measured by the Healthy Eating Index–2005 (HEI). Our data consists of U.S. adults who participated in the 2003–2004 National Health and Nutrition Examination Survey. Alternative instrumental variable estimators explicitly address issues of endogeneity and complex sample design. Our empirical analysis demonstrates that diet quality is strongly interrelated with food culture. We suggest that vitamin consumption serves as another marker for healthy eating. This finding emphasizes the need to employ economic modeling when developing public policy to reduce obesity.